2017
DOI: 10.1038/ng.3938
|View full text |Cite
|
Sign up to set email alerts
|

Condensin-mediated remodeling of the mitotic chromatin landscape in fission yeast

Abstract: The eukaryotic genome consists of DNA molecules far longer than the cells that contain them. They reach their greatest compaction during chromosome condensation in mitosis. This process is aided by condensin, a ‘Structural Maintenance of Chromosomes’ (SMC) family member1,2. The spatial organization of mitotic chromosomes and how condensin shapes chromatin architecture are not yet understood. Here, we use chromosome conformation capture (Hi-C)3,4 to study mitotic chromosome condensation in the fission yeast S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 46 publications
6
125
0
Order By: Relevance
“…Our in situ Hi-C data in the fission yeast system reveal that condensin mediates the organization of the 300 kb–1 Mb large domains and that those large domains are formed during mitosis and gradually degrade during the following phases. The mitotic domains formed by condensin have also been detected in recent Hi-C and ChIA-PET studies 21,35 . It has been suggested that human chromosomes are devoid of topological domains, including TADs and larger domains, such as compartments A and B, during mitosis 13,15 .…”
Section: Discussionmentioning
confidence: 67%
“…Our in situ Hi-C data in the fission yeast system reveal that condensin mediates the organization of the 300 kb–1 Mb large domains and that those large domains are formed during mitosis and gradually degrade during the following phases. The mitotic domains formed by condensin have also been detected in recent Hi-C and ChIA-PET studies 21,35 . It has been suggested that human chromosomes are devoid of topological domains, including TADs and larger domains, such as compartments A and B, during mitosis 13,15 .…”
Section: Discussionmentioning
confidence: 67%
“…Our observations suggest that the activity of the condensin complex may be dispensable for telomere and chromosome arm separation in meiosis II. To verify this, we expressed SPB (Cdc11-CFP, red) and telomere (Taz1-GFP, green) markers cells bearing a conditional shutoff allele for the condensin subunit Cut14 Smc2 (combining promoter repression with an auxininducible degron) (Kakui et al, 2017). To determine the effect of condensin degradation on chromosome arm and telomere separation, we analyzed the number of telomere foci with respect to spindle size in meiosis I and II ( Fig.7 A-C).…”
Section: Condensin Is Required For Telomere and Chromosome Arm Separamentioning
confidence: 99%
“…However, to specifically inhibit Aurora kinase in meiosis II, image acquisition started exactly 10min after the spreading of cells on the imaging media containing 1-NA-PP1 and only cells starting meiosis II were filmed. This protocol allows imaging of cells that underwent normal chromosome segregation in meiosis I. condensin depletion was performed using the cut14-so strain previously described (Kakui et al, 2017) that combines transcriptional repression of cut14 under the nmt81 thiaminerepressible promoter and Cut14 depletion using an Auxin-Inducible Degron (AID) system. To induce condensin depletion, the imaging media was supplemented with 0.5mM of 1-Naphthaleneacetic acid (Sigma) and 5μg/ml of thiamine.…”
Section: Aurora Kinase Inhibition and Condensin Depletion 18mentioning
confidence: 99%
“…These axis-like structures, named vermicelli , are reminiscent of the localization of condensin to mitotic chromosomes. In Wapl-deficient cells, long-range chromosomal contacts were increased, with concomitant loss of compartments [12]; this resembles the characteristic landscape of mitotic chromosomal contacts, which is organized by condensin [13,14]. Thus, under certain conditions, cohesin has the potential to organize similar axial structures as condensin.…”
Section: Chromosome Organization By Smc Complexesmentioning
confidence: 99%